VISI MISI DAN TUJUAN DIUTUSNYA RASULULLAH SAW - Hanton (El-Rusyd, 2016)
Prophet as the messenger of Allah is very professional in every efforttoward the changes he made to humanize humans, that humans walking inaccordance with nature, in disseminating the vision and mission of Islam,the Qur'an and hadith as a major source of Islamic teachings alreadygiven instructions and the basic principles of education, so it should be asolution to address the educational crisis that occurred. Because it is aplanned activity, education should have the clarity of vision, mission andgoals to be achieved. Of us can imagine how it would be if there is anactivity without having a clear vision and mission.